A Natural Dye-Sensitized from Pare (Bitter Gourd) Leaves Extracts for Dye-Sensitized Solar Cell (Dssc) - Ramadhani, Wahidah Febriya; Suriani S, Suriani S; Aisyah A, Aisyah A; Iswadi I, Iswadi I (Al-Kimia, 2019)
The availability of energy sources is dwindling so a renewable energy which has a potential chance to be developed, such as solar panels, is needed. The use of solar panels is still quite expensive in terms of manufacturing process. For this reason, a cheap solar panel based is developed, and it is called DSSC (Dye-Sensitized Solar Cell). The use of DSSC is developed in Indonesia, a country which is famous for its biological richness. In this study, pare leaves were used as photosensitizers obtained from the extraction process of maceration by various solvents. The DSSC test was done on four extracts including N-hexane extract, Ethyl Acetate, Methanol, and Combination of the three extracts. The highest value of efficiency obtained from each extract respectively are 0,03%, 0,04%, 0,14% and 0,30%. Characterization was done by examining the UV-Vis and FTIR spectral data. The result of UV-Vis analysis shows that wavelength for N-hexane, Ethyl Acetate, Methanol, and Combined extracts are 269,1 nm, 668,0 nm, 663,9 nm, and 6631 nm, respectively. FTIR results found that the chromophore and auxochrome groups were identified on all four tested extracts, namely; C = C, C = O, -OH, and -C-H groups.